Women at Work: A Study of the Glass Ceiling Phenomenon among Managerial Women in Ghana - Gyekye, D. (University of Ghana, 2013)
Studies conducted in recent times have indicated that women’s advancement into top echelon positions in organizations have been hindered by the glass ceiling barrier. The present study sought to identify the authenticity of this finding among managerial women in the Ghanaian context and how these barriers can be overcome. Using the Miles and Huberman’s approach, the in-depth interview responses of twelve women managers from four organizations in middle and senior levels were content analysed after they were purposively sampled out of the population. Results of the study revealed the following as barriers to women’s efforts in climbing the career ladder: same-sex rivalry, work-family conflict, gender role socialization and lack of initiative. Of the barriers found, work-family conflict was found to be the most prevalent. The study also found that organizational/ institutional support, mentoring, personality; time management and personal sacrifice were ways by which women believed these barriers can be broken. These findings are consistent with earlier findings that women encounter the glass ceiling barrier whilst climbing to the top.
Thesis (MPHIL)-University of Ghana, 2013